The influence of hydrogen sulfide on wheatgrass (Triticum æstivum L.) de-etiolation - Kristić, Marija (Array, 2020)
Hydrogen sulfide (H2S) is involved in many physiological processes and responses to the abiotic types of stress. The aim of the study was to determine the effect of sodium hydrogen sulfide (NaHS) and the time of application on the physiological properties of etiolated wheatgrass plants. Two genotypes of wheatgrass were grown under controlled conditions for five days without light and then with a 12-hour photoperiod, watered for three consecutive days with 100, 200, and 500 mM NaHS solutions. The plants were watered in three variants, 7-9, 10-12, and 13-15 days after sowing, respectively. The highest content of phenols, flavonoids, and hydrogen peroxide was found in wheatgrass plants watered with 100 mM of NaHS solution. The highest proline content and lipid peroxidation levels were found in the plants at 500 mM of NaHS solution. Also, the significant influence of the watering period on the examined physiological parameters was determined. The results show that H2S significantly affects the de-etiolation process and concentration of physiologically active compounds in wheatgrass plants.